Toxic Positivity: The Other Side of the Concept to Always Be Positive in All Conditions - Kojongian, Monica Geaby Rivana; Wibowo, Doddy Hendro (Psychopreneur Journal, 2022)
Toxic Positivity is known as the concept of over-promotion of happiness. This concept believes that staying positive by ignoring negative emotions is the right solution in dealing with problems. This misconception about the concept of staying positive is not in accordance with the fact that negative emotions are unavoidable from human life. This qualitative research with a phenomenological approach focuses on the subjective or psychological experiences of two victims of toxic positivity in their social relationships, starting with the responses, feelings and impacts that arise when they get toxic positivity. The findings show that toxic positivity is considered an inappropriate motivational response. Giving a toxic positivity response gives rise to feelings of not being understood, angry and disappointed, the negative impact is not only physical but also psychological. The perpetrators are considered to come from individuals who have never experienced the same problem before and lack empathy. In addition, the sentence toxic positivity is also found in verbal abuse.